Prevalence of Methicillin-Resistant Staphylococcus aureus Among Radiology Technicians in Hospitals in Misurata, Libya. - Alwashsiah, Mohanned; Almogassbi , Mohamed; Elzwawi, Elham (AlQalam Journal of Medical and Applied Sciences, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of healthcare-associated infections, and healthcare workers (HCWs) can serve as potential reservoirs for transmission. Data on MRSA colonization among radiology technicians, particularly in Libya, are limited. To estimate the prevalence of MRSA among radiology technicians in Misurata, Libya, and to describe antimicrobial resistance patterns and potential occupational factors. A cross-sectional study was conducted in two hospitals in Misurata between May and June 2024. Hand swabs were collected from radiology technicians and processed using standard microbiological methods. MRSA identification was based on Clinical and Laboratory Standards Institute (CLSI) guidelines. Data were analyzed using descriptive and inferential statistics with 95% confidence intervals. Of 60 participants, 66.7% carried bacteria; Staphylococcus aureus accounted for 85% of isolates, of which 76.5% were MRSA. The overall prevalence of MRSA colonization among radiology technicians was 43.3% (95% CI: 27–61%). Ciprofloxacin resistance was observed in 23.1% of MRSA isolates. Exploratory analyses suggested higher MRSA carriage among less experienced technicians and those working in Computed Tomography (CT), although these associations were not statistically significant. This study provides preliminary evidence of MRSA carriage among radiology technicians in Misurata. While limited by sample size, sampling method, and restricted antimicrobial testing, the findings suggest that radiology departments should be considered in broader infection prevention discussions. Further multicenter and molecular studies are required to confirm these observations and to inform tailored infection control strategies.